Measles vaccine coverage indices in Brazil: integrative literature review (Research, Society and Development, 2020)
Objective: analizar producciones científicas sobre las tasas de cobertura de vacunación contra el sarampión en Brasil de 2015 a 2019. Method: it is an Integrative Literature Review. The databases: MEDLINE, LILACS and BDENF were used. Complete articles were selected and available in Portuguese and Spanish. The results were analyzed using the IRAMUTEQ software, specifically by analyzing similarity and word cloud. Results: analyzed using IRAMUTEQ, three categories were categorized: Need for vaccination as a preventive action in the population; Not vaccinating and the relationship with the child's health status; and The need to monitor measles vaccination status as a means of disease prevention. Conclusion: it is concluded that the study made it possible to recognize the profile of measles vaccination coverage, since, even after being eradicated, it still has low vaccination coverage, and it is essential that health professionals actively participate in an active search.